Performance modelling of adaptive routing communication networks in multi-cluster systems under bit-reversal traffic. (1st January 2014) - Sharifi, Hojjat; Akbari, Mohammad K.; Javadi, Bahman
Several analytical models of interconnection networks of multi-cluster systems under uniform traffic pattern have been proposed in the literature. However, there has been hardly any work reported yet that deals with other important non-uniform traffic patterns found in many parallel applications. In this paper we propose a new analytical model of adaptive routing in fat-tree-based interconnection networks in the presence of traffic pattern generated by bit-reversal permutation, which is an important communication operation in parallel applications such as FFT computations. The model is validated through comprehensive simulation, through which the proposed model exhibited a good degree of accuracy for various system organisations and under different working conditions.